Belize : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Outlook and risks. The economy will remain vulnerable over the medium term, with sluggish real GDP growth, rising public debt and widening external current account deficits. International reserves could decline to uncomfortably low levels. The financial system would continue to be hampered by high NPLs and low capital buffers, especially at a systemic bank. Main fiscal risks include a court decision that could lead to a larger than expected compensation to the former owners of the nationalized companies, weaknesses in a systemic bank, and the cost of the new public bank. Focus of the Consultation. Discussions focused on measures that would place public debt on a sustainable path; address weaknesses in the financial system, particularly in a systemic bank; buttress external sector resilience; and enhance competitiveness and inclusive growth. Key policy advice. ? Improve the primary fiscal balance to about 4.5 percent of GDP starting in 2015. This could be achieved mainly by allowing spending on goods and services to rise only in line with inflation; containing the expansion in the wage bill; requiring public workers to contribute to their pensions; and by widening the tax base and strengthening revenue administration. Active debt management, including refinancing of expensive debt with low-earning deposits (essentially from PetroCaribe), would support these efforts. ? Address banking sector vulnerabilities through improving capital buffers. ? Improve public financial management (PFM) to contain low-quality spending, strengthen budget formulation, preparation, and execution, and improve the coverage and accuracy of budget documents. ? Further improve the business environment to attract more private investment, boost competitiveness, and enhance job-creating and inclusive growth. Implementation of staff advice. Implementation of recent staff advice is mixed. The breathing room provided by the debt restructuring was not used to improve the primary fiscal balance. The authorities plan to review exemptions and zero-ratings under the GST.